Organic field effect transistor with a novel poly(linoleic acid)-g-poly(methyl methacrylate)-g-poly(D,L-lactide) graft copolymer insulator using a PEDOT:PSS composite electrode - Demir, A.; Allı S.; Allı A.; Kösemen A. (Springer New York LLC, 2019)
This study presents a one-pot process used to synthesize novel poly(linoleic acid)-g-poly(methyl methacrylate)-g-poly(D,L-lactide) (PLina-g-PMMA-g-PLA (PLiMALA-3)) graft copolymers. The process was carried out by combining the free radical polymerization (FRP) of methyl methacrylate with the ring-opening polymerization (ROP) of D,L-lactide from polymeric linolenic acid having peroxide groups in the main chain. The characterization of the graft copolymers was performed using proton nuclear magnetic resonance, gel permeation chromatography, thermal gravimetric analysis (TGA) and differential scanning calorimetry (DSC) techniques. Afterwards, an organic field effect transistor (OFET) was fabricated with the novel poly(linoleic acid)-g-poly(methyl methacrylate)-g-poly(D,L-lactide) graft copolymer (PLiMALA-3) as the insulator layer. Poly(3-hexylthiophene) (P3HT) was used as the active layer and pre-patterned OFET substrates were used as the source/drain electrodes. In order to measure capacitance, an ITO/(PLiMALA-3)/PEDOT:PSS structure was prepared using the same method. For electrical characterization of the OFET, the device was held in the dark at room temperature in ambient air in order to determine the characteristics of the output and transfer current–voltage (I-V). The main parameters of the device, which included the threshold voltage (VTh), field effect mobility (?FET) and current on/off ratio (Ion/Ioff), were determined by measuring the capacitance–frequency (C–f) plot of the ITO/Polymer/PEDOT:PSS structure. Results showed that the fabricated OFET device exhibited good performance including low VTh, comparable mobility and Ion/Ioff. © 2019, Springer Science+Business Media, LLC, part of Springer Nature.